Norvaline is accumulated after a down-shift of oxygen in Escherichia coli W3110 - Soini, Jaakko (BioMed Central, 2008)
BACKGROUND: Norvaline is an unusual non-proteinogenic branched-chain amino acid which has been of interest especially during the early enzymological studies on regulatory mutants of the branched-chain amino acid pathway in Serratia marcescens. Only recently norvaline and other modified amino acids of the branched-chain amino acid synthesis pathway got attention again when they were found to be incorporated in minor amounts in heterologous proteins with a high leucine or methionine content. Earlier experiments have convincingly shown that norvaline and norleucine are formed from pyruvate being an alternative substrate of α-isopropylmalate synthase, however so far norvaline accumulation was not shown to occur in non-recombinant strains of E. coli. RESULTS: Here we show that oxygen limitation causes norvaline accumulation in E. coli K-12 W3110 during grow in glucose-based mineral salt medium. Norvaline accumulates immediately after a shift to oxygen limitation at high glucose concentration. On the contrary free norvaline is not accumulated in E. coli W3110 in aerobic cultures. The analysis of medium components, supported by transcriptomic studies proposes a purely metabolic overflow mechanism from pyruvate into the branched chain amino acid synthesis pathway, which is further supported by the significant accumulation of pyruvate after the oxygen downshift. The results indicate overflow metabolism from pyruvate as necessary and sufficient, but deregulation of the branched chain amino acid pathway may be an additional modulating parameter. CONCLUSION: Norvaline synthesis has been so far mainly related to an imbalance of the synthesis of the branched chain amino acids under conditions were pyruvate level is high. Here we show that simply a downshift of oxygen is sufficient to cause norvaline accumulation at a high glucose concentration as a consequence of the accumulation of pyruvate and its direct chain elongation over α-ketobutyrate and α-ketovalerate. Although the flux to norvaline is low, millimolar concentrations are accumulated in the cultivation broth, which is far above the level which has been discussed for being relevant for misincorporation of norvaline into recombinant proteins. Therefore we believe that our finding is relevant for recombinant protein production but also may even have implications for the physiology of E. coli under oxygen limitation in general.